Education As Human Resource Investment: Educational Resources And Education As An Industry - Baroroh, Fatimatul; Nurrochim, Nurrochim; Ratnaningsih, Sita (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Education serves as a future investment for the people of Indonesia. It encompasses not only physical aspects but also non-physical dimensions. Non-physical investment is better known as human resource investment. This study aims to describe education as a human resource investment and to explore its potential as an industry. Using a qualitative approach with a library research method, data analysis was conducted by reducing data, reviewing it, and drawing conclusions. The findings reveal that treating education as an investment involves managing the field of education seriously, akin to an industry. The education industry belongs to the service sector. In this sector, the most effective promotion is customer recommendations (students) based on satisfaction with the services received during and after transactions. Customers in the education industry, namely students or learners from an institution, exhibit unique characteristics compared to customers in other service sectors. A notable distinction is the prolonged engagement period of customers. Moreover, the increasing demand for formal education, particularly higher education, signifies its growing importance in meeting societal needs.